2020
DOI: 10.1002/cam4.3309
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in mortality‐to‐incidence ratios by race/ethnicity for female breast cancer in New York City, 2002‐2016

Abstract: Background Racial disparities in New York City (NYC) breast cancer incidence and mortality rates have previously been demonstrated. Disease stage at diagnosis and mortality‐to‐incidence ratio (MIR) may present better measures of differences in screening and treatment access. Racial/ethnic trends in NYC MIR have not previously been assessed. Methods Mammogram rates were compared using the NYC Community Health Survey, 2002‐2014. Breast cancer diagnosis, stage, and mortality were from the New York State Cancer Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In recent years, more light has been shed on the inherent disparities that exist within the health care system in the United States. These inequalities have been well documented in the [8][9][10] Socioeconomic status and race have also been shown to correlate with treatment delays for women with breast cancer. 15 These discrepancies are thought to be attributable in part to lack of access to early screening and early diagnosis and lack of appropriate screening intervals in disadvantaged populations.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In recent years, more light has been shed on the inherent disparities that exist within the health care system in the United States. These inequalities have been well documented in the [8][9][10] Socioeconomic status and race have also been shown to correlate with treatment delays for women with breast cancer. 15 These discrepancies are thought to be attributable in part to lack of access to early screening and early diagnosis and lack of appropriate screening intervals in disadvantaged populations.…”
Section: Discussionmentioning
confidence: 93%
“…Multiple studies have shown that Black and Latino patient populations have more advanced disease at initial diagnosis of breast cancer as compared with White women, in addition to a slower decrease in disease-related mortality over time. 8–10 Socioeconomic status and race have also been shown to correlate with treatment delays for women with breast cancer. 15 These discrepancies are thought to be attributable in part to lack of access to early screening and early diagnosis and lack of appropriate screening intervals in disadvantaged populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding race/ethnicity, it was recently determined to be associated with the prognosis of breast cancer ( 36 39 ). Especially, young black women with breast cancer had more adverse pathological factors and worse prognosis, when compared with white or Asian women.…”
Section: Discussionmentioning
confidence: 99%